Identification of macrophage correlated biomarkers to predict the prognosis in patients with intrahepatic cholangiocarcinoma - Xu, Linping; Yan, Meimei; Long, Jianpeng; liu, Mengmeng; Yang, Hui; Li, Wei (Frontiers in Oncology, 2022)
Background: It has been shown that tumor-associated immune cells, particularly macrophages, play a fundamental role in the development and treatment response of intrahepatic cholangiocarcinoma (ICC). However, little is known about macrophages at the single cellular level of ICC patients. Methods: ScRNA-seq was used in the present study to identify the genes differentially expressed in ICCs. Furthermore, IHC and flowcytometry were used to confirm the findings. Kaplan-Meier and TIDE scores were also used for prognostic analysis and ICB responses. Results: A significant number of macrophages were found in ICCs as compared to adjacent tissues. We then extracted, processed, and classified the macrophages from the ICCs and adjacent tissues into 12 clusters. Significantly, the macrophages from the ICC exhibited an immunosuppressed state in terms of both signature gene expression and functional enrichment. Furthermore, our results indicate that, of the 10 selective tumor-promoting genes of macrophages, only MMP19 and SIRPα can predict ICB responses in ICCs. Although a higher expression of MMP19 and SIRPα predict a poor prognosis for ICCs without immunotherapy after surgery, patients with high SIRPα expression were more sensitive to immunotherapy, whereas those with high MMP19 expression were not sensitive to immunotherapy. To define the mechanisms, we found that SIRPαhi ICCs exhibited an increased enrichment KEGG pathway of leukocyte transendothelial migration and neutrophil extracellular trap formation. The increased immune cell infiltration will increase sensitivity to immunotherapy. Conclusion: Collectively, macrophages are critical to the immune status of ICCs, and MMP19 and SIRPα can predict prognosis and ICB responses for ICCs.